DETEKSI KEDIPAN MATA PADA VIDEO MENGGUNAKAN OPEN CV - Haruno Sajati; Anggraini Kusumaningrum; Bagus Budi Utomo (Compiler, 2017)
In the development of technology in the current era is one of the most rapid progress, it is marked by almost all managers of data and information has been done with the computer because of the increasingly diverse information issues handled, Detection of objects is one of the most important early stages before Done object recognition process. Eye blink detection can be used to open a new file or an application. In this research use case detection eye blinking on video using OpenCV to open notepad application. The blink detection uses the haar cascade classifier method for realtime detection and the  OpenCV Library. The first step determines the pattern 1111100000. Next enter the video sample avi format to match with a predetermined pattern. In this program the system managed to detect the eye according to the pattern by circling the eye area when the eyes are open or literate and when the eyes closed or brake there is no circle in the eye area for the correct video sample.